Migrasi Internasional dan Kondisi Kesehatan Anak yang Ditinggalkan di Jawa Barat dan Jawa Timur - Idris Ihwanudin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2019)
International migration affects children who are left behind in their homes. One of the impacts is the health conditions of migrant children. When a child is left by a parent to migrate, the daily activities and life of the child will become a little lame due tono role ofone or both parents who care for and care for health, education, and behavior. This article discusses the impact of international migration on parents on children's health conditions and health behavior and care of migrant children. The data used is the result of CHAMPSEA 2016 study which focuses on the conditions of children and families of international migrants. The results show that international parental migration didnot have a major influence on the health conditions of children, migrant children only experience mild health problems without experiencing serious health problems,such as severe illness and physical / mental disabilities. The behavior of migrant children towards health and the role of caregivers of migrant children contributedto the child's health condition. Good health behavior of migrant children and good care still does not rule out the possibility of developing mild health problems.